2022
DOI: 10.3389/fcvm.2022.992879
|View full text |Cite
|
Sign up to set email alerts
|

PAH-specific therapy for pulmonary hypertension and interstitial lung disease: A systemic review and meta-analysis

Abstract: ObjectivePulmonary hypertension (PH) in context with interstitial lung disease (ILD) portends serious clinical consequences and a high rate of mortality. Recently published randomized controlled trials (RCTs) which assessed the pulmonary arterial hypertension (PAH)-specific drugs for pulmonary hypertension and interstitial lung disease (PH-ILD) revealed inconsistent clinical outcomes with previous studies. We conducted a systemic review and meta-analysis to further investigate the effect of PAH-specific therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…However, the inhaled administration of treprostinil or NO has been found to be a promising treatment strategy with clinical efficacy in PH-ILD. 99 Results from the INCREASE trial (a Multicenter, Randomized, Double-Blinded, Placebo-Controlled Trial to Evaluate the Safety and Efficacy of Inhaled Treprostinil in Subjects With Pulmonary Hypertension Due to Parenchymal Lung Disease) demonstrated that patients with ILD-PH treated with inhaled treprostinil had significant improvements in exercise, as shown by clinically relevant changes in the 6minute walking distance between the two groups. 100 In addition, a subgroup analysis of patients with IPF demonstrated that treatment with inhaled treprostinil was associated with significant improvements in forced vital capacity (FVC), although the mechanism was unclear.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inhaled administration of treprostinil or NO has been found to be a promising treatment strategy with clinical efficacy in PH-ILD. 99 Results from the INCREASE trial (a Multicenter, Randomized, Double-Blinded, Placebo-Controlled Trial to Evaluate the Safety and Efficacy of Inhaled Treprostinil in Subjects With Pulmonary Hypertension Due to Parenchymal Lung Disease) demonstrated that patients with ILD-PH treated with inhaled treprostinil had significant improvements in exercise, as shown by clinically relevant changes in the 6minute walking distance between the two groups. 100 In addition, a subgroup analysis of patients with IPF demonstrated that treatment with inhaled treprostinil was associated with significant improvements in forced vital capacity (FVC), although the mechanism was unclear.…”
Section: Treatmentmentioning
confidence: 99%
“…However, the inhaled administration of treprostinil or NO has been found to be a promising treatment strategy with clinical efficacy in PH–ILD. 99…”
Section: Pulmonary Hypertension In Interstitial Lung Diseasementioning
confidence: 99%
“…Although anti-fibrotic drugs, effective for IPF and certain other progressive fibrotic ILDs, improve FVC and slow disease advancement, their impact on PH development requires additional investigation. Standard use of medications approved for treating PAH is not advised for the treatment of PH-ILD patients as their safety and effectiveness in this particular patient group remain uncertain [100]. Nevertheless, registry data suggest occasional prescriptions on an individual basis.…”
Section: Management and Treatmentmentioning
confidence: 99%